Preparation of Biomass-Immobilized Platinum Nanoparticle Catalyst Layer

Through the preparation method of biomass-fixed platinum nanoparticle catalyst layer, the problems of complex construction process and poor bending durability of the existing hydrogen fuel cell catalyst layer are solved, and efficient catalytic performance of oxygen reduction reaction and higher discharge power density are achieved.

CN115425246BActive Publication Date: 2025-04-29JIANGSU PURE STATE INTELLIGENT ELECTRICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211061577.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-01
Publication Date
2025-04-29
Estimated Expiration
2042-09-01

AI Technical Summary

Technical Problem

The existing hydrogen fuel cell catalyst layer construction process is complex and has poor bending durability, resulting in lower performance of H2-air fuel cells than commercial H2-O2 fuel cells.

Method used

The preparation method of biomass-fixed platinum nanoparticle catalyst layer was successfully prepared by immersing eggplant flakes into a Nafion solution containing H2PtCl6, adsorbing PtCl62- and Nafion precursors, and then lyophilized and pyrolyzed treatment.

Benefits of technology

The built integrated catalyst layer has excellent catalytic performance of oxygen reduction reaction (ORR), a half-wave potential value of 0.805V, a discharge power density of 246Wcm-2, and has better performance than membrane electrodes prepared with powdered commercial Pt/C catalysts, and has better oxygen and electron transport capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115425246B_ABST
    Figure CN115425246B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a catalyst layer with immobilized platinum nanoparticles on biomass, comprising the following steps: cutting an eggplant, a biomass material with O-functional groups rich on its surface, into thin slices; immersing the thin slices of eggplant in a Nafion solution 6 containing H2PtCl6 to fully adsorb the precursors of PtCl6 2‑ and Nafion; after freeze-drying treatment, a spongy eggplant adsorbed with PtCl6 2 - and Nafion, i.e., eggplant-PtCl6 2‑ / Nafion film is obtained; pyrolyzing the eggplant-PtCl6 2‑ / Nafion film in a furnace under a flowing Ar atmosphere to generate an electrode catalyst. The present invention has successfully developed a method for an electrode of a catalyst layer with immobilized ultrafine Pt nanoparticles. This catalyst has excellent oxygen reduction activity, low oxygen mass transfer resistance, and low electron transfer resistance. Based on this catalyst, an H2-air fuel cell assembled at 2000 mA cm ‑2 has a power density of 1.3 W cm ‑2 , and its performance is superior to that of a membrane electrode prepared with a powdered commercial Pt / C catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hydrogen fuel cell, and in particular to the preparation of a biomass-fixed platinum nanoparticle catalyst layer. Background Art

[0002] Among various electrochemical devices, hydrogen fuel cells have the advantages of high theoretical energy density, no pollution, and high efficiency, which have aroused great interest in the energy field. Scaled hydrogen fuel cells have great application potential in electric energy storage systems where power networks regulate daytime loads. However, there are still many challenges in the development of efficient H2-air fuels. First, efficient oxygen reduction reaction (ORR) catalysts with faster kinetics and higher thermodynamic activity are the key to high efficiency. Second, although many very promising ORR catalysts have been reported in recent years, including commercial Pt / C and PtCo / C, they all show excellent ORR performance. However, due to the lack of a reasonable catalyst layer construction process, the performance of H2-air fuel cells is much lower than that of currently commercial H2-O2 fuel cells. In addition, the construction of efficient oxygen transfer and electron transfer catalyst layers is also the key to the application of efficient H2-air fuel cells. Therefore, the construction of more efficient catalyst layers is of great significance to promote the application of H2-air fuel cells.

[0003] At present, there are mainly the following methods for constructing the catalyst layer of hydrogen fuel cells: The most commonly used method is to prepare the catalyst layer by brushing some polymer binders (such as polytetrafluoroethylene and Nafion) on the surface of a flexible conductive carrier (such as carbon paper, carbon cloth, metal foam or proton exchange membrane), which is found to have complex processes and poor bending durability. The second method, which is also used in commercial hydrogen fuel cells, makes catalyst and carbon powder, PTFE, Nafion and carbon fiber into catalyst layer paper, which is then attached to the proton exchange membrane. The catalyst layer structure prepared by this method is relatively stable, but a large amount of catalyst is required. In recent years, a new type of integrated catalyst layer structure has also been widely reported. On the one hand, this integrated construction strategy effectively combines the catalyst synthesis process with the air electrode construction process. On the other hand, this integrated electrode may have a negative impact on the material (O2, OH - , e - ) transport. For example, Wang et al. reported an integrated catalyst layer with oxygen- and nitrogen-coordinated copper species that could achieve 88.5 mWcm -2 The high power density of H2-air fuel cells is expected to be high, and they have excellent cycling stability when directly assembled into Zn-air batteries. However, to date, there has been no study on the gas transfer impedance of the catalyst layer of H2-air fuel cells. Summary of the invention

[0004] In view of the defects in the prior art, the purpose of the present invention is to provide a preparation method for a biomass-fixed platinum nanoparticle catalyst layer.

[0005] The preparation of the biomass-fixed platinum nanoparticle catalyst layer provided by the present invention comprises the following steps:

[0006] Step S1: cutting the biomass material eggplant having a surface rich in O functional groups into thin slices;

[0007] Step S2: Immerse the eggplant slices in a Nafion solution containing H2PtCl6 to fully adsorb PtCl6 2- and Nafion precursors;

[0008] Step S3: After freeze drying, the adsorbed PtCl6 is obtained 2 - and Nafion sponge eggplant, i.e. eggplant-PtCl6 2- / Nafion membrane;

[0009] Step S4: Eggplant-PtCl6 2- The electrode catalyst was generated by pyrolysis of the Nafion film in a furnace under a flowing Ar atmosphere.

[0010] Preferably, step S2 is specifically as follows: immersing the 1-3% Nafion solution in 5-15mM H2PtCl6 for 10-15h to fully adsorb PtCl6 2- and Nafion precursor.

[0011] Preferably, the step S3 is specifically as follows: freeze-drying for 40-60 hours to obtain adsorbed PtCl6 2 - and Nafion's spongy eggplant.

[0012] Preferably, the step S4 is specifically: eggplant-PtCl6 2- The electrode catalyst was obtained by pyrolysis of the Nafion film at 700-900°C in a tube furnace under flowing Ar atmosphere for 4-6 hours.

[0013] Preferably, the electrode catalyst is used as a catalyst for a biomass-derived graphite electrode, and the preparation of the biomass-derived graphite electrode comprises the following steps:

[0014] Step M1: cutting the biomass material eggplant having a surface rich in O functional groups into thin slices;

[0015] Step M2: then immersing the eggplant slices in the Nafion solution to fully absorb the Nafion precursor;

[0016] Step M3: After freeze drying, a sponge-like eggplant adsorbed with Nafion, i.e., an eggplant-Nafion membrane, is obtained;

[0017] Step M4: Pyrolysis of the eggplant-Nafion film in a tube furnace under a flowing Ar atmosphere to obtain a biomass-derived graphite electrode;

[0018] Step M5: After the obtained electrode was stirred in deionized water at room temperature for several hours, the obtained flaky pure carbon support was represented as biomass-derived graphite carbon support.

[0019] Preferably, the step M2 specifically comprises: immersing the eggplant slices in a 2% Nafion solution for 12 hours to fully absorb the Nafion precursor.

[0020] Preferably, the step M3 specifically comprises: after freeze-drying for 48 hours, a sponge-like eggplant adsorbed with Nafion, namely, an eggplant-Nafion film, is obtained.

[0021] Preferably, the step M4 specifically comprises: pyrolyzing the eggplant-Nafion film at 800° C. for 5 hours in a tubular furnace under a flowing Ar atmosphere to obtain a biomass-derived graphite electrode.

[0022] Preferably, the step M5 is specifically as follows: after stirring the obtained electrode in 100 mL of deionized water at room temperature for 5 hours, the obtained flaky pure carbon support is obtained.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention combines the synthesis of Pt-based catalysts and the construction process of the catalyst layer to successfully prepare an integrated catalyst layer, and uses it as an application study for H2-air fuel cells. From the material characterization, it can be seen that the ultrafine Pt nanoparticles are successfully fixed into the catalyst layer through a simple one-step biomass-derived carbon thermal curing reduction process. The constructed integrated catalyst layer has excellent ORR catalytic performance with a half-wave potential value of 0.805V. At the same time, the Pt-CL / PEM / Pt-CL electrodes are assembled into an H2-air fuel cell with a power density of 246W at a discharge power of 1.2000mA cm-2. cm-2 , which outperforms membrane electrodes prepared with powdered commercial Pt / C catalysts. It is worth noting that compared with electrodes prepared by traditional processes, the present invention has better oxygen and electron transport capabilities. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0026] Figure 1 (a) is a SEM image of the Pt-CL film at 5 μm in an embodiment of the present invention;

[0027] Figure 1 (b) is a SEM image of the Pt-CL film at 2 μm in an embodiment of the present invention;

[0028] Figure 2 (a) TEM and HRTEM images of Pt-CL in an embodiment of the present invention;

[0029] Figure 2 (b) is the XRD pattern of commercial Pt / C and Pt-CL in the examples of the present invention;

[0030] Figure 2 (c) is the N2 adsorption-desorption isotherm of Pt-CL in the embodiment of the present invention;

[0031] Figure 2 (d) is the corresponding pore size distribution of Pt-CL in the embodiment of the present invention;

[0032] Figure 3 (a) is the cyclic voltammetry (CV) curve of Pt-CL and commercial Pt / C catalyst in O2-saturated 0.1M HClO4 solution in the embodiment of the present invention;

[0033] Figure 3 (b) is the linear sweep voltammogram (LSV) response of Pt-CL and commercial Pt / C in the embodiment of the present invention;

[0034] Figure 3 (c) is the LSV curve of Pt-CL measured in an O 2 saturated 0.1 M HClO 4 solution with a surprising rotation rate in an embodiment of the present invention;

[0035] Figure 3 (d) is a Koutecky-Levich (K–L) Pt-CL diagram in an embodiment of the present invention;

[0036] Figure 4 (a) is a resume diagram of PECMC records based on Pt-CL and Pt / C in an embodiment of the present invention;

[0037] Figure 4 (b) is a comparison chart of Pt ECSA values ​​based on Pt-CL and Pt / C in the embodiments of the present invention;

[0038] Figure 4 (c) is the IV polarization and power density curves obtained for commercial Pt / C and Pt-CL catalyst-based PEMFCs in the embodiments of the present invention;

[0039] Figure 4 (d) is a comparison chart of the cathode resistances R, R1 and R2 of Pt-CL in the embodiment of the present invention and commercial Pt / C-based cathodes;

[0040] Figure 5 The Pt-CL in the embodiment of the present invention is 100, 400, 1000 and 2000 mA cm -2 Impedance spectrum of

[0041] Figure 6 Flow chart of the steps for preparing a biomass-fixed platinum nanoparticle catalyst layer in an embodiment of the present invention. DETAILED DESCRIPTION

[0042] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0043] In an embodiment of the present invention, the preparation of the biomass-immobilized platinum nanoparticle catalyst layer provided by the present invention adopts a simple biomass-derived carbon thermal curing reduction process to prepare an ultrafine Pt nanoparticle immobilized catalyst layer (Pt-CL), comprising the following steps:

[0044] Step S1: cutting the biomass material eggplant having a surface rich in O functional groups into thin slices;

[0045] Step S2: Immerse the eggplant slices in a 2% Nafion solution containing 10 mM H2PtCl6 for 12 h to fully adsorb PtCl6 2- and Nafion precursor;

[0046] Step S3: After freeze drying for 48 hours, the adsorbed PtCl6 2 - and Nafion sponge eggplant, i.e. eggplant-PtCl6 2- / Nafion membrane;

[0047] Step S4: Eggplant-PtCl6 2- The electrode catalyst was obtained by pyrolysis of the Nafion film at 800 °C in a tube furnace under flowing Ar atmosphere for 5 h.

[0048] Here, mM is the abbreviation of mmol, which means millimole.

[0049] In the embodiment of the present invention, when preparing the electrode of the pure carbon layer, a biomass-derived graphite carbon carrier (BC) is first prepared by a simple one-step heat treatment process.

[0050] The eggplant, a biomass material having surface rich O functional groups, is cut into thin slices;

[0051] Then, the eggplant slices were immersed in 2% Nafion solution for 12 h to fully adsorb the Nafion precursor;

[0052] After freeze-drying for 48 h, the sponge-like eggplant adsorbed with Nafion, i.e., eggplant-Nafion membrane, was obtained;

[0053] The electrode was obtained by pyrolysis treatment of eggplant-Nafion film at 800 °C for 5 h in a tube furnace under flowing Ar atmosphere;

[0054] After the obtained electrode was stirred in 100 mL of deionized water at room temperature for 5 h, the obtained flaky pure carbon support was denoted as biomass-derived graphitic carbon support (BC).

[0055] In the present embodiment, the phase structure of Pt-CL and BC samples was measured by X-ray diffraction (XRD). The microstructure, morphology and elemental mapping of the prepared samples were characterized by field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) with energy dispersive X-ray spectrometer. Samples with porous distribution and special surface area were tested by nitrogen adsorption with the help of Brunuer-Emmett-Teller (BET) equation.

[0056] In the present embodiment, the electrochemical measurements were performed on an electrochemical workstation (CHI 760D, CH Instruments, Inc., Shanghai, China) and a PINE rotating disk electrode (RDE) system (Pine Instruments Co. Ltd., USA). A standard three-electrode electrochemical cell equipped with a gas flow system was used during the measurement.

[0057] Prior to the measurement, the electrodes were first polished with 5.0, 3.0, and 0.05 μm alumina slurries in sequence using a rotating disk electrode (RDE, 5.0 mm in diameter), followed by ultrasonic washing with water and ethanol for 1 min, respectively. The cleaned electrodes were dried with high-purity nitrogen vapor. The ground Pt-CL catalyst ink was prepared by dispersing Pt-CL catalyst (5.0 mg) into a mixture containing 100 μL Nafion solution (0.5 wt %) and 900 μL ethanol, followed by ultrasonic treatment for 2 min. Afterwards, 12 μL of the catalyst ink was then cast onto the glassy carbon (GC) electrode surface, resulting in a catalyst loading of 305 μg cm -2 For comparison, a commercial Pt / C catalyst ink was also prepared using the same process as the catalyst ink.

[0058] The ORR performance of the catalysts was studied by cyclic voltammograms (CV) and linear sweep voltammograms (LSV) in 0.1 M HClO4 solution saturated with O2 (or N2). -1 Measured at a scan rate of .

[0059] At different disk rotation rates of 400, 625, 900, 1225, 1600, and 2025 rpm, the voltage was measured at 10 mV s -1 The LSV curves were measured at a scan rate of .

[0060] All potentials in this work were recorded at a Ag / AgCl reference electrode. The number of electrons transferred per oxygen molecule during the ORR process (n) was calculated using the Koutecky-Levich (KL) equation:

[0061]

[0062] B=0.62nF(D0) 2 / 3 v -1 / 6 C0 (2)

[0063] J k =nGkC0 (3)

[0064] Where, J is the current density measured during ORR, J k is the kinetic current density, ω is the electrode rotation angular velocity (ω = 2πN, N is the linear rotation speed), B is the slope of the KL graph, n represents the number of electron transfers per oxygen molecule, and F is the Faraday constant (F = 96 485C mol-1 ), D0 is the diffusion coefficient of O2 in 0.1M HClO4, and v is the dynamic viscosity (0.01cm 2 s -1 ), C0 is O2(1.2×10 -3 mol L -1 ) volume concentration.

[0065] In the present embodiment, when assembling MEA into PEMFCs (proton exchange membrane fuel cells) and operating the fuel cell, a Pt / CL catalyst ink for ultrasonic spray deposition was prepared by mixing 60wt% Pt / CL catalyst, Nafion ionomer solution, isopropanol and pure water.

[0066] When 60 wt% Pt / CL catalyst was used, the mass ratio of ionomer binder to carbon black (I / C) was adjusted to 0.95 / 1. Anode and cathode CL were directly deposited onto Nafion 212 membrane using an automatic ultrasonic sprayer.

[0067] Pt-CL catalyst was prepared by directly immersing Pt-CL catalyst-based MEA into Nafion solution. The catalyst layer was hot-pressed directly onto Nafion 212 proton exchange membrane as cathode electrode.

[0068] The performance of the single cell was tested using a Scribner 850e fuel cell test system from Scribner Associates, Inc. The experiments were conducted at a cell temperature of 80°C and an ambient pressure of 100 kPa. abs ) and the relative humidity was 100% RH. For H2-Air, ultrapure gas (Ar, H2 or Air) was supplied to the anode and cathode, respectively, under a stoichiometric flow condition of 2 / 2.5.

[0069] All experiments started with membrane rupture by first holding the cell voltage at 0.60 V in H2 air for 2 h, and then alternating between 0.70 V and 0.40 V for 20 cycles, with each voltage held for 10 min.

[0070] Figure 1 (a) is a SEM image of the Pt-CL film at 5 μm in an embodiment of the present invention. Figure 1 (b) is a SEM image of the Pt-CL film at 2 μm in an embodiment of the present invention. Figure 1 As shown, an integrated membrane electrode with ultrafine Pt nanoparticles immobilized catalyst layer (Pt-CL) was developed using a simple one-step biomass-derived carbon thermal curing reduction process.

[0071] The preparation process of Pt-CL mainly includes three steps. First, eggplant-PtCl6 was obtained by immersing eggplant slices in an aqueous solution of hexachloroplatinic acid hexahydrate and 2% Nafion. 2- ;

[0072] Then the stabilized eggplant-PtCl6 2- Cast onto glass plate and dry into a viscous flexible film;

[0073] Eggplant-PtCl6 was prepared by pyrolysis at 800 °C under Ar 2- The film produced a flexible thin film of Pt-CL.

[0074] The three-dimensional carbon layer can be seen from the top view of Pt-CL. Figure 1 (b) shows that the Pt-CL film is composed of disordered carbon black aggregates with a high aspect ratio, which may be more conducive to improving the electron transport capacity of the electrode.

[0075] In the embodiment of the present invention, the conductivity of the Pt-CL film prepared by the present invention reaches 23500S m-1In contrast, commercial CL is mainly composed of carbon spheres with a width of about 50-80 mm. The conductivity of commercial CL is 21000 S m -1 .

[0076] Figure 2 (a) is the TEM and HRTEM images of Pt-CL in the embodiment of the present invention, Figure 2 (b) is the XRD pattern of commercial Pt / C and Pt-CL in the embodiment of the present invention, Figure 2 (c) is the N2 adsorption-desorption isotherm of Pt-CL in the embodiment of the present invention, Figure 2 (d) is the corresponding pore size distribution of Pt-CL in the embodiment of the present invention, such as Figure 2 As shown, by HRTEM ( Figure 2 a) and XRD( Figure 2 b) The structural and compositional information of CL containing Pt nanoparticles was analyzed, where the distorted graphitic carbon structure with a high degree of graphitization can be clearly observed.

[0077] TEM and high-resolution TEM (HRTEM) images showed that nanoscale Pt particles (2–5 nm) were uniformly distributed on the biomass-derived carbon supports.

[0078] At the same time, XRD results show that the phase structure and metal particle size of the Pt-CL catalyst prepared by the present invention are the same as those of the commercially available Pt / C catalyst, further proving that the present invention has successfully loaded nano-Pt nanoparticles onto biomass-derived carbon carriers. Figure 2 c and Figure 2 d) The pore structures of the carbon supports were compared. From the results, it can be seen that the catalyst prepared from biomass eggplant has a larger micro-nano channel structure, which is conducive to the establishment of more three-phase interfaces in the catalytic layer, thereby increasing the intrinsic activity of the catalyst, including MA and ECSA, and thus improving its hydrogen fuel cell performance.

[0079] In the present embodiment, the three-electrode test method was first used to evaluate the catalyst in 0.1 M HC l ORR activity in O4 solution. Cyclic voltammetry (CV) curves show that the biomass-derived Pt-CL has the same ORR activity as commercial Pt / C, such as Figure 3 (a) shown.

[0080] Figure 3(b) shows the linear sweep voltammogram (LSV) response of Pt-CL and commercial Pt / C. It can be clearly seen that the onset potential (and half-wave potential) of the prepared Pt-CL to Pt-CL and commercial Pt / C are 0.97 (0.805) and 0.96 (0.796), respectively. Obviously, the almost identical onset and half-wave potential values ​​of Pt-CL and commercial Pt / C indicate that Pt-CL has superior ORR activity. In addition, Figure 3 (c) shows the O with unusual rotation rate 2 LSV curve of Pt-CL measured in saturated 0.1M HClO4 solution. Figure 3 (c) and Figure 3 The corresponding Koutecky-Levich (KL) in (d) shows that the average value of the number of transferred electrons at 0.30 to 0.45 V is calculated to be 4.0 for Pt-CL, which is close to the theoretical value of Pt catalyst (n = 4.0), indicating a near four-electron ORR process. The above results show that under the three-electrode evaluation system, Pt-CL in the present embodiment has the same catalytic performance as the commercial Pt / C catalyst.

[0081] In an embodiment of the present invention, Figure 3 (a) Cyclic voltammetry (CV) curves of Pt-CL and commercial Pt / C catalysts in O2-saturated 0.1 M HClO4 solution at a scan rate of 50 mV s -1 . Figure 3 (b) Linear sweep voltammogram (LSV) curves of Pt-CL and commercial Pt / C catalysts in O2-saturated 0.1 M HClO4 solution at a scan rate of 10 mV s -1 , the rotation speed is 1600rpm. Figure 3 (c) Linear sweep voltammogram (LSV) curves of Pt-CL obtained at different rotation rates in O2-saturated 0.1 M HClO4 solution. The scan rate is 10 mV s -1 . Figure 3 Koutecky–Levich (K–L) Pt-CL diagram in (d), derived from c at different potentials.

[0082] The catalysts were further evaluated using a membrane electrode (MEA) system. For the preparation process of the corresponding MEA, please refer to the experimental section.

[0083] In the inventive examples, the mass activity and electrochemical active area (ECSA) of the prepared Pt-CL and commercial catalysts were first evaluated. It can be seen that the MA of the Pt-CL catalyst prepared in the present invention and the commercial Pt / C catalyst are both 183.6 and 164.7 A. mg-1 Pt . Figure 4 a shows the CVs recorded for Pt-CL and Pt / C based PEMFCs, indicating that all PEMFCs have similar characteristics of H2 adsorption / desorption between 0.075 V and 0.40 V and oxide layer formation between 0.60 V and 1.15 V. The corresponding Pt ECSA values ​​are evaluated and shown in Figure 4 (b). The Pt ECSA values ​​calculated from the hydrogen adsorption charge at 100% RH are 62 m 2 g Pt -1 and 58m 2 g Pt -1 , for Pt-CL and commercial Pt / C based MEA, respectively. These Pt ECSA values ​​are comparable to those reported in a recent publication by the present inventors for a higher loaded P / CL cathode CL. Figure 4 c shows the typical IV polarization curves evaluated for Pt-CL and a commercial Pt / C-based PECPC with similar Pt loading. From the IV polarization curves, it can be clearly seen that the Pt-CL-based cathode has a high conductivity at 100, 400, 1000, and 2000 mA cm -2 The cell voltages at 100, 400, 1000, and 2000 mA cm -2 The cell voltages are 0.855, 0.798, 0.719 and 0.613 V respectively. The results show that the H2 fuel cell has a good polarization curve and discharge power density. Figure 4 In (d), R is the internal resistance, R1 is the resistance, and R2 is the mass transfer resistance.

[0084] In order to further explore the catalytic mechanism of the cathode layer formed by different catalysts, the present invention further studied the MEA at 100, 400, 1000 and 2000 mA / cm -2 The impedance spectrum under Figure 5 As shown. Figure 4 (d) It can be seen that the Pt-CL in the embodiment of the present invention and the commercial Pt / C-based cathode have similar high-frequency resistance (R) and resistance (R1), indicating that the prepared Pt-CL and commercial Pt / C-based MEA have the same electron and proton transport process. In addition, the Pt-CL cathode has a smaller mass transfer resistance (R2), so the Pt-CL cathode shows a higher discharge power density.

[0085] In summary, the ultrafine Pt nanoparticles immobilized catalyst layer electrode w was successfully developed through a simple biomass-derived carbon thermal curing reduction process. Based on the prepared integrated catalyst layer, it has excellent oxygen reduction activity. At the same time, the Pt-CL-based MEA has a low oxygen mass transfer resistance, so at 2000mA cm -2 The following assembled a 1.246W cm -2 High power density H2-air fuel cell.

[0086] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A preparation method for a biomass-fixed platinum nanoparticle catalyst layer, characterized in that: The steps include: Step S1: cutting the biomass material eggplant having a surface rich in O functional groups into thin slices; Step S2: Immerse the eggplant slices in a Nafion solution containing H2PtCl6 to fully adsorb PtCl6 2- and Nafion precursors; Step S3: After freeze drying, the adsorbed PtCl6 is obtained 2 - and Nafion sponge eggplant, i.e. eggplant-PtCl6 2- / Nafion membrane; Step S4: Eggplant-PtCl6 2- The electrode catalyst was generated by pyrolysis of the Nafion film in a furnace under a flowing Ar atmosphere.

2. The preparation of the biomass-immobilized platinum nanoparticle catalyst layer according to claim 1, characterized in that: The step S2 is specifically as follows: immersing the 1-3% Nafion solution in 5-15mM H2PtCl6 for 10-15h to fully adsorb PtCl6 2- and Nafion precursor.

3. The preparation of the biomass-immobilized platinum nanoparticle catalyst layer according to claim 1, characterized in that: The step S3 is specifically as follows: after freeze drying for 40-60 hours, the adsorbed PtCl6 2 - and Nafion's spongy eggplant.

4. The preparation of the biomass-immobilized platinum nanoparticle catalyst layer according to claim 1, characterized in that: The step S4 is specifically as follows: 2- The electrode catalyst was obtained by pyrolysis of the Nafion film at 700-900°C in a tube furnace under flowing Ar atmosphere for 4-6 hours.

5. The preparation of the biomass-immobilized platinum nanoparticle catalyst layer according to claim 1, characterized in that: The electrode catalyst is used as a catalyst for a biomass-derived graphite electrode, and the preparation of the biomass-derived graphite electrode comprises the following steps: Step M1: cutting the biomass material eggplant having a surface rich in O functional groups into thin slices; Step M2: then immersing the eggplant slices in the Nafion solution to fully absorb the Nafion precursor; Step M3: After freeze drying, a sponge-like eggplant adsorbed with Nafion, i.e., an eggplant-Nafion membrane, is obtained; Step M4: Pyrolysis of the eggplant-Nafion film in a tube furnace under a flowing Ar atmosphere to obtain a biomass-derived graphite electrode; Step M5: After the obtained electrode was stirred in deionized water at room temperature for several hours, the obtained flaky pure carbon support was represented as biomass-derived graphite carbon support.

6. The preparation of the biomass-immobilized platinum nanoparticle catalyst layer according to claim 5, characterized in that: The step M2 specifically includes: immersing the eggplant slices in a 2% Nafion solution for 12 hours to fully absorb the Nafion precursor.

7. The preparation of the biomass-immobilized platinum nanoparticle catalyst layer according to claim 5, characterized in that: The step M3 is specifically as follows: after freeze drying for 48 hours, a sponge-like eggplant adsorbed with Nafion, namely, an eggplant-Nafion film, is obtained.

8. The preparation of the biomass-immobilized platinum nanoparticle catalyst layer according to claim 5, characterized in that: The step M4 is specifically as follows: pyrolysis treatment of the eggplant-Nafion film at 800° C. for 5 hours in a tubular furnace under a flowing Ar atmosphere to obtain a biomass-derived graphite electrode.

9. The preparation of the biomass-immobilized platinum nanoparticle catalyst layer according to claim 5, characterized in that: The step M5 is specifically as follows: after stirring the obtained electrode in 100 mL of deionized water at room temperature for 5 hours, the obtained flaky pure carbon carrier is obtained.

Citation Information

Patent Citations

  • Production of solid polymer electrolyte-catalyst composite electrode

    JP1999217687A

  • Manufacturing method of cathode electrode for fuel cells and cathode electrode for fuel cells

    US20120135320A1